Redes de cooperação: o processo de mudança organizacional em empresas associadas à ASIUSI - um estudo de caso - Peretti, Jucelda de Lourdes Gonzatto (My University, 2014)
This work investigates the process of organizational change which occurred in companies once they entered an interorganizational network. The study contributes for the understanding of the change approach used by companies, which is required for its adequacy to organizational network. The bibliographical review carried through the work catches a glimpse on concepts and formats of companies networks, on the Cooperation Network Program (Programa Redes de Cooperação), and on different approaches to the process of organizational change. The case study was carried out at the Association of Machining Industry (Associação Serrana das Indústrias de Usinagem - ASIUSI), a metal-mechanical network, integrant of the Cooperation Network Program developed by the Secretariat for the Development and International Affairs of the State of Rio Grande do Sul (SEDAI) which was placed in operation by the University of Caxias of Sul (UCS). The data were collected through personal interviews with the representative members of the associated companies. This comparison showed that most phases of the changes process in the surveyed enterprises identifies itself with the theoretical approaches which they were compared, except for the phases that treated with specific aspects of the organizational framework which they are inserted. The results were compared with five approaches to organizational change found in the literature. Providing the limitations of this study are observed, it is expected that the conclusions obtained may help to implement improvements in building organizational models write similar characteristics.
Este trabalho investiga o processo de mudança organizacional ocorrido em empresas a partir de sua inserção em uma rede interorganizacional. O estudo contribui para o entendimento da abordagem de mudança utilizada pelas empresas, necessária para a adequação da mesma ao formato organizacional de rede. A revisão bibliográfica realizada ao longo do trabalho vislumbra conceitos e formatos sobre redes de empresas, sobre o Programa Redes de Cooperação e sobre diferentes abordagens do processo de mudança organizacional. O estudo de caso foi realizado na Associação Serrana das Indústrias de Usinagem (ASIUSI), uma rede do setor metal-mecânico, integrante do Programa Redes de Cooperação que é desenvolvido pela Secretaria do Desenvolvimento e dos Assuntos Internacionais do Estado do Rio Grande do Sul (SEDAI) e operacionalizado pela Universidade de Caxias do Sul (UCS). Os dados foram coletados junto aos representantes das empresas na Associação, através de entrevistas e interpretados por meio da análise de conteúdo. O resultado da análise foi comparado com cinco abordagens de mudanças organizacionais. A comparação evidenciou que a maioria das fases da estrutura de mudanças nas empresas pesquisadas se identifica com as abordagens teóricas as quais foram comparadas, excetuando-se as fases que tratam de aspectos específicos ao formato organizacional ao qual as mesmas estão inseridas. Respeitando-se as limitações do estudo, espera-se que as conclusões obtidas sirvam para implementar melhorias na metodologia de formação e consolidação de modelos organizacionais com características semelhantes.
Keywords: Administração de empresas; Redes interorganizacionais; O Programa Redes de Cooperação; Mudanças organizacionais; Interorganizational network; The Cooperation Network Program; Organizational change